The antimicrobial resistance patterns and associated determinants in Streptococcus suis isolated from humans in southern Vietnam, 1997-2008 - Chau Nguyen VV; Campbell James I; Baker Stephen; Wolbers Marcel; Anh Pham H; Mai Nguyen TH; Nghia Ho DT; Chieu Tran TB; Hoa Ngo T; Hien Tran T; Farrar Jeremy; Schultsz Constance (BMC Infectious Diseases, 2011)
Abstract Background Streptococcus suis is an emerging zoonotic pathogen and is the leading cause of bacterial meningitis in adults in Vietnam. Systematic data on the antimicrobial susceptibility profiles of S. suis strains isolated from human cases are lacking. We studied antimicrobial resistance and associated resistance determinants in S. suis isolated from patients with meningitis in southern Vietnam. Methods S. suis strains isolated between 1997 and 2008 were investigated for their susceptibility to six antimicrobial agents. Strains were screened for the presence and expression of tetracycline and erythromycin resistance determinants and the association of tet(M) genes with Tn916- like transposons. The localization of tetracycline resistance gene tet(L) was determined by pulse field gel electrophoresis and Southern blotting. Results We observed a significant increase in resistance to tetracycline and chloramphenicol, which was concurrent with an increase in multi-drug resistance. In tetracycline resistance strains, we identified tet(M), tet(O), tet(W) and tet(L) and confirmed their expression. All tet(M) genes were associated with a Tn916-like transposon. The co-expression of tet(L) and other tetracycline resistance gene(s) encoding for ribosomal protection protein(s) was only detected in strains with a minimum inhibitory concentration (MIC) of tetracycline of ≥ 64 mg/L Conclusions We demonstrated that multi-drug resistance in S. suis causing disease in humans in southern Vietnam has increased over the 11-year period studied. We report the presence and expression of tet(L) in S. suis strains and our data suggest that co-expression of multiple genes encoding distinct mechanism is required for an MIC ≥ 64 mg/L to tetracycline.